Electrochemical co-deposition of Ni–Gd2O3 for composite thin targets preparation: Production of 155Tb as a case study. (August 2022) - Wang, Yizheng; Sounalet, Thomas; Guertin, Arnaud; Haddad, Férid; Michel, Nathalie; Nigron, Etienne
Abstract: In the last years, 155 Tb has attracted enormous interest due to its potential role in theranostics in nuclear medicine. To estimate its production yield, the aim of this study was to develop a method to prepare thin Gd-enriched-containing targets aimed at the 155 Gd(d, 2n) 155 Tb nuclear cross section measurement. To this end, the electrochemical co-deposition method has been chosen to manufacture Ni–Gd2 O3 composite targets. Several process parameters that have an impact on the deposit quality, have been investigated to increase the incorporation of Gd mass (up to 3 mg). To validate the concept, seven targets made by natural Gd were irradiated with deuteron beams at the GIP ARRONAX facility cyclotron, with an energy range ranging from 8 MeV to 30 MeV to extract the cross section values by using the stacked-foils method. Results obtained turned out to have great consistency with existing published data thus validating the proposed method. Therefore, an alternative target manufacturing concept aimed at cross section measurement is presented in this work. Highlights: Terbium cross section of the deuteron-induced reaction on natural gadolinium. Manufacturing gadolinium-nickel composite targets by electrodeposition. Incorporation of gadolinium in alkaline aqueous solution. Target design for the production of terbium from enriched gadolinium.